MT1JP/miR-103a-3p induce pyroptosis and regulate the tumor immune microenvironment in gastric cancer - Yongbin Zhang; Fubin Ma; Lin Wang; Chenglou Zhu; Junyou Shi; Mingxu Da (Scientific Reports)
Abstract Immune checkpoint blockade (ICB) has made great progress in treating cancer, regulating the tumor immune microenvironment can improve the efficacy of ICB and has become a major focus. Pyroptosis, as a new form of cell death, has been reported in a few diseases to activate cellular immune responses due to the release of inflammatory factors. This may offer a new approach for regulating the tumor immune microenvironment. MT1JP plays an important role in gastric cancer, but its mechanism of pyroptosis and immunity is unclear. Bioinformatics analysis combined with qRT-PCR revealed the expression levels of MT1JP and miR-103a-3p in GC cells and tissues, and their interactions were revealed by dual-luciferase assay and rescue experiment. The effects of MT1JP on GC cell proliferation, invasion, and migration were assessed by CCK-8, EdU, Colony formation, Wound healing, and Transwell. Western blot, IHC, IF, and ELISA were used to assess the effects of MT1JP/miR-103a-3p in GC cell pyroptosis and immunity. MT1JP expression was downregulated and miR-103a-3p was upregulated in GC cells and tissues, the expression of MPDZ was downregulated in AGS and MKN-45. Overexpression of MT1JP inhibited GC cell proliferation, invasion, and migration. MT1JP directly targets and inhibits miR-103a-3p. MT1JP/miR-103a-3p induced the expression of pyroptosis-related proteins (GSDMD, NLRP3, Caspase1) and inflammatory factors (IL-1β, IL-18), activated the immune pathway Sting/IFN-β, and downregulated PD-L1. Based on bioinformatics analysis and preliminary exploration in this study, MPDZ may be a potential downstream target of miR-103a-3p. MT1JP/miR-103a-3p can induce pyroptosis, activate the immune response, and then inhibited the growth of gastric cancer, possibly acting through MPDZ. This explored a new anti-cancer method to regulate the tumor immune microenvironment.